Pendampingan Halal: Dorong UMKM Sonopakis Lor Kabupaten Bantul Berdaya Saing - Wuku Astuti; Aswan Aswan; Rizqi Septiana Wulandari; Marselino Yance Momot (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aimed to enhance the understanding of culinary MSME actors in Padukuhan Sonopakis Lor, Kasihan, Bantul, regarding halal product concepts, critical points in ingredients and production processes, and to prepare them for obtaining halal certification. The methods applied included educational and participatory approaches, consisting of MSME identification, halal product education, guidance in identifying ingredients and production processes, preparation of supporting documents, and evaluation with follow-up. The activities involved seven MSME participants and included interactive counseling, assistance in preparing ingredient lists and production flow, and uploading documents to the SIHalal platform. The results showed improved understanding of halal principles and certification processes, better-prepared documents for Self Declare submission, awareness of separating halal and non-halal production, and increased confidence in marketing certified halal products. Additionally, MSME actors were provided marketing strategies through social media, WhatsApp groups, and food delivery platforms, making their products not only compliant with halal standards but also more accessible to consumers. In conclusion, halal product education and mentoring effectively enhance local MSMEs' competitiveness, strengthen product credibility, and expand market opportunities.